(Table 1) Sample description, carbon and tetrapyrrole pigments at DSDP Hole 61-462 - Earl W Baker; William Louda (PANGAEA, 1981)
Six core-samples from DSDP/IPOD Site 462 in the Central Nauru Basin were examined for tetrapyrrole pigment content. Samples ranged from Pliocene to middle Cretaceous, and were recovered from 25 to 551 meters sub-bottom. The fate of chlorophyll in an open ocean environment was to be the prime objective of this study. Leg 61 is viewed as an extension of tetrapyrrole pigment studies in the western and southwestern Pacific which included the Japan Trench sites of Legs 56-57 (Louda et al., in press; Baker and Louda, in press a), the Shikoku Basin and Daito Ridge sites of Leg 58 (Baker and Louda, 1980), and the Mariana Basin and Trench sites of Leg 60 (Baker and Louda, in press b). Throughout these studies, we have detected tetrapyrrole pigments which by their quantity and quality could be related to the overall productivity of overlying waters, depositional environments, and certain geologic events, such as reworking. The more-oceanic position of Site 462 and suspected turbidite deposition in the deep ocean basin in which it is situated seemed favorable for relating rate of pigment loss to oxic diagenesis.
Supplement to: Baker, EW; Louda, W (1981): Geochemistry of chlorophyll derivatives: Deep Sea Drilling Project Leg 61, Site 462, northern Nauru Basin. In: Larson, RL; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 61, 619-620, https://doi.org/10.2973/dsdp.proc.61.119.1981